First example of the correlated calculation of the one-bond tellurium-carbon spin-spin coupling constants Relativistic effects, vibrational corrections, and solvent effects - Rusakova, Irina L (Journal of computational chemistry, 2016)
© 2016 Wiley Periodicals, Inc.